Microsoft Office Access 2007 Introductory - J. OLeay Timothy (Mc Graw Hill, 2007)
Timothy and Linda O'Leary and the Computer Information Technology Team at McGraw-Hill Higher Education offer your students a fully integrated learning program with time-tested quality and reliability. It’s theme of “Making Office Relevant” helps students understand why they need this course and these skills. Student success is assured through clear step-by-step instruction, plentiful screen captures and conceptual explanations. Each Lab, designed to be covered in 1 hour of class time, combines conceptual coverage with detailed software-specific instructions. Each Lab opens with a running case study that highlights real-world applications of each software program and leads students from problem to solution. The O'Leary Series helps students learn specific applications skills along with those that cross all Office applications, which is especially important in mastering this version of Office. This Introductory version, versus the Brief version, contains more content including 3 additional labs.